Application of Self Directed Learning Model to Improve Student's Independence and Critical Thinking Skills - Wasyilah Wasyilah; Yusrizal Yusrizal; Suhrawardi Ilyas (Jurnal Penelitian Pendidikan IPA, 2021)
The lack of active involvement of students in learning is caused by the lack of students' skills in critical thinking, for example, by asking questions, expressing opinions, and solving problems so that students only memorize existing concepts, theories, and formulas without wanting to dig further to be understood in depth. This study aims to determine the increase in independence and critical thinking skills on momentum and impulse material at SMAN 9 Banda Aceh. The method in this study was quasi-experimental, then the instruments used were questionnaire sheets, observation sheets, and questions. The results of the study indicate that the application of the Self Direct Learning learning model can increase student learning independence. The results of the t-test analysis (independent sample t-test) obtained a significance value of 0.000 <0.05, meaning that there is a significant difference in the average learning independence of students in the experimental class and the control class. The application of the self-directed learning model can improve students' critical thinking skills. The results of the analysis of students' Critical Thinking Skills obtained a significance value of 0.000 <0.05, meaning that there was a significant average difference between students' critical thinking skills in the experimental class and the control class. The conclusion in this study proves that the Self Direct Learning model can increase students' learning independence and Critical Thinking Skills on momentum and impulse materials